A magyar kormányok konvergencia programjai a választási ciklusok szorításában - Gősi, János (Jelenkori Társadalmi és Gazdasági Folyamatok, 2007)
Hungarian convergency programmes are trapped in the four-year political cycles. The logic of the parliamentary elections - because of the danger of failure - let fiscal restrictions to be implemented only in the first two years. This is extremely true for general structural reforms, from what the public and the political parties longing for victory expect serious results after 2-3 years of hardship.